2014
DOI: 10.1044/2013_ajslp-13-0024
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Construct Validity of the V-RQOL in Speakers Who Use Alaryngeal Voice

Abstract: The results indicate that some V-RQOL questions do not align with their proposed domains. Consequently, an alternative scoring algorithm may be warranted for alaryngeal populations, and the authors make suggestions for this change that are simple and efficient. Based on the findings of the present factor analysis, use of this modified scoring procedure may serve to increase the sensitivity of the V-RQOL for those who are laryngectomized and use alaryngeal methods of voice and speech. Consequently, the value an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 22 publications
(36 reference statements)
0
5
0
Order By: Relevance
“…Another study showed that only two questions do not apply to this particular population. The authors suggested adjusting the scores to improve the instrument's sensitivity (12). Studies analysing other voice disorders also found a similar correlation between the V-RQOL and VHI (59,60).…”
Section: ' Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Another study showed that only two questions do not apply to this particular population. The authors suggested adjusting the scores to improve the instrument's sensitivity (12). Studies analysing other voice disorders also found a similar correlation between the V-RQOL and VHI (59,60).…”
Section: ' Discussionmentioning
confidence: 88%
“…Studies investigating quality of life after total laryngectomy have used several instruments. However, most of these studies use a single questionnaire, or they apply one specific voice and one specific cancer to assess different forms of rehabilitation when more than one are associated (9,(10)(11)(12)(13)(14)(15)(16). Previous studies have compared different instruments for monitoring quality of life after cancer treatment but without detailing the variable of phonatoric rehabilitation (17)(18)(19).…”
Section: ' Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Vocal Handicap Index (VHI) [36] and VHI-10 [37] show mild-moderate handicap in alaryngeal speakers [38][39][40][41]and the VoiSS [42] was sufficiently sensitive to demonstrate poorer outcomes for salvage compared to primary laryngectomy. The Voice Related Quality of Life (VRQOL) has been used in a number of alaryngeal investigations [40,[43][44][45][46][47] and has the added advantage of having undergone an investigation of construct validity for alaryngeal voice [46]. This involved factor analysis [46] which suggested that alaryngeal speakers interpret some questions from an awareness of the social impact of their voice due to its difference to that of laryngeal speakers.…”
Section: Self-rating Scales/questionnairesmentioning
confidence: 99%
“…The Voice Related Quality of Life (VRQOL) has been used in a number of alaryngeal investigations [40,[43][44][45][46][47] and has the added advantage of having undergone an investigation of construct validity for alaryngeal voice [46]. This involved factor analysis [46] which suggested that alaryngeal speakers interpret some questions from an awareness of the social impact of their voice due to its difference to that of laryngeal speakers. The authors considered the tool's validity with this patient group would be increased if these questions were rephrased or moved from the physical to the social-emotional domain section.…”
Section: Self-rating Scales/questionnairesmentioning
confidence: 99%